HUBUNGAN DISIPLIN KERJA, LINGKUNGAN KERJA DAN BUDAYA KERJA TERHADAP KINERJA KARYAWAN DI PT. TAMBAK GELUNG WINDU KENCANA SAKTI SITUBONDO DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Wahyudi Wahyudi; Lita Permata Sari; Riska Ayu Pramesthi (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
Human resources are the most important factor in a company's goal achievement. Without organized human resources, a company or agency cannot operate effectively and achieve its goals. The purpose of this study is to analyze the influence of Work Discipline, Work Environment, and Work Culture on Performance with Job Satisfaction as an intervening variable. This research is an explanatory study. The population in this study were employees of PT. Tambak Gelung Windu Kencana Sakti Situbondo. The sampling technique was determined by simple random sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model-Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that Work Discipline has a significant effect on Job Satisfaction, Work Environment has no significant effect on Job Satisfaction, Work Culture has a significant effect on Job Satisfaction, Work Discipline has a significant effect on Performance, Work Environment has no significant effect on Performance, Work Culture has a significant effect on Performance, Job satisfaction has no significant effect on Performance. The results of the indirect influence hypothesis test show that the variable Work Discipline on Performance through Job Satisfaction has a positive but insignificant effect, Work Environment on Performance through Job Satisfaction has a positive but insignificant effect, Work Culture on Performance through Job Satisfaction has a positive but insignificant effect.